Variation in Labor Induction over the Days of the Week - Falciglia, Gustave H.; Grobman, William A.; Murthy, Karna (American Journal of Perinatology, 2015)
Objective To quantify the variation in induction of labor (IOL) over the days of the week for gravid women in the United States.Study Design Women who delivered singletons between 24 and 42 weeks' gestation were identified using birth certificate data from 2007 to 2010. Women with pregnancy-associated hypertension, fetal anomalies, previous cesarean delivery, or incomplete records were excluded. The primary outcome was IOL. Women were stratified into four gestational age groups: < 34, 34 to 36, 37 to 38, and ≥ 39 weeks. Frequencies of IOL were determined according to day of the week. Multivariable logistic regression estimated the association between weekend delivery and IOL, adjusting for maternal characteristics and year of delivery.Results There were 11.6 million eligible women. For each gestational age stratum, the frequency of IOL was increased on weekdays compared with weekends (8.0 vs. 7.4%, 16.5 vs. 13.2%, 25.0 vs. 14.8%, and 33.2 vs. 19.3% at < 34, 34–36, 37–38, and ≥ 39 weeks, respectively; p < 0.01 for all). Multivariable analyses demonstrated that weekend IOL was inversely related to gestational age (odds ratios: 0.93, 0.77, 0.52, and 0.48, respectively; p < 0.001 for all).Conclusion The frequency of IOL varies according to the day of the week, with the odds of weekend IOL lowest at greater gestational ages.
Keywords: induction of labor; late preterm; early term; variation; epidemiology